Revitalisasi Pendidikan Karakter KH. Hasyim Asy’ari dalam Kitab Adāb Al-‘Ālim Wa Al-Muta’allim - Syarif Maulidin; Nurul Vazilatul Umayah; Ulin Nuha (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This research aims to examine the thoughts of K.H. Hasyim Asy'ari in the book Adāb Al-'Ālim Wa Al-Muta'allim is related to the revitalization of character education. The background to this research is based on the importance of character education in shaping the morality and integrity of the younger generation, especially in the context of Islamic education. The method used is library research with a qualitative approach, which collects data from the works of K.H. Hasyim Asy'ari and other relevant literature. The research results show that K.H.'s thinking Hasyim Asy'ari in this book contains character education values ​​that can be applied to improve the current education system, such as the importance of simplicity, honesty and moral awareness. This finding has the implication that K.H. Hasyim Asy'ari can be used as a basis for developing a character education curriculum based on Islamic values, in order to form a better generation in the future.